Kajian waktu penangkapan ikan Kurisi Bali (Etilis sp) dengan pancing ulur di perairan teluk Manado - Ivor Lembondorong Labaro; Revols D.Ch. Pamikiran; Hariyani Sambali (Universitas Sam Ratulangi, 2022)
Demersal fish species, such as Red snappers (Etelis sp.), have high economic value and are in high demand in both domestic and export markets. The fishing gear used by fishermen in the Manado Bay waters to catch demersal fish, especially Red snappers, is the bottom hand line. The lack of complete information about the distribution of the Red snappers in their habitat, the size of the fish and the fishing time and techniques are the main problems.This study is aimed at providing the legal size, fishing technique, and fishing season in relation with feeding period, bait type, and correct fishing grounds for red snapper Etelis sp.. The study utilized explorative method through direct observations and interviews. During the study, 986 individuals of red snappers were caught, 517 individuals in morning operation and 469 in afternoon operation. On monthly basis, there were 270 fish caught in July, 165 fish in February, 154 fish in January and the rest was distributed in other months. Red snappers Etelis sp. were caught mostly at 04:30-05:00 in the morning and 17:01-17:30 in the afternoon. The fish catches consisted of size range of >620 mm TL (110 ind), 630-700 mm TL (452 ind), 710-760 mm TL (333 ind), and 770-800 mm TL (91 ind).